Biological monitoring of polycyclic aromatic hydrocarbons. Metabolites in urine. - Jongeneelen, Frans J; Bos, Rob P; Anzion, R B; Theuws, J L; Henderson, P T (Scandinavian Journal of Work, Environment & Health, 1986)
Assays of urinary mutagenicity, urinary 3-hydroxy-benzo(a)pyrene, and urinary 1-hydroxypyrene were used to study their suitability in estimating exposure to polycyclic aromatic hydrocarbons (PAH) in coal tar products. Rats exposed to coal tar solutions applied on the dorsal skin excreted mutagens, 3-hydroxy-benzo(a)pyrene, and 1-hydroxypyrene dose dependently in their urine. The correlation between the three parameters was high. Five dermatologic patients undergoing topical coal tar treatment excreted low concentrations of 3-hydroxy-benzo(a)pyrene and high concentrations of 1-hydroxypyrene. A significant correlation between the excretion of the two metabolites was found. The smoking workers of a coal tar distillation plant showed a significantly enhanced urinary mutagenicity compared with their nonsmoking colleagues, but an increase due to occupational exposure was not found. However, the concentration of 1-hydroxypyrene in the urine of these workers highly exceeded the upper 95 percentile of a reference population. The urinary excretion of 1-hydroxypyrene of smoking referents was not significantly increased compared with that of nonsmoking referents. The data suggest that urinary 1-hydroxypyrene is a sensitive and specific marker for the assessment of occupational exposure to PAH.